The Military's Strangest Campaigns & Characters : Extraordinary but True Tales from Military History - Quinn, Tom (London Robson, 2006)
Provides a look at some of the finest battles ever to be fought. This book presents about a 100 stories, such as the extraordinary 'Battle That Never Was' between two Celtic tribes that never began, the ill-fated launch of the Russian warship Novgorod and the Victoria Cross winner who seemed absolutely determined to die, yet survived, and more.
Keywords: Military history